PROXIMAL RENAL TUBULES ENZYMURIA AS A SCREENING TEST IN PATIENTS WITH SERONEGATIVE SPONDYLOARTHROPATHIES - Spasovski, Dejan; Sandevska, Emilija; Balkanov, Svetlana Krstevska; Vaslievska, Ana; Jakupi, Ljindita Djemaili; Cvetinovska, Elena; Iseini, Kujtim; Selimi, Mediha; Mitreski, Vladimir; Chamurovski, Nikola; Dimitrovska, Maja Jakimovska (Journal of Morphological Sciences, 2023)
The aims of this study are: to compare diagnostic values and laboratory variables of alanine aminopeptidase (microsomal AAP), Î³-glutamyl transferase (Î³-GT), Î²2-microglobulin (Î²2-M), C-Reactive Protein (CRP), and the index for disease activity (PASI) in the early diagnosis of previously untreated psoriatic arthritis (Psa) and to see how untreated psoriatic arthritis affected tubular function and the sensitivity of the brush border region, together with the diagnostic value of enzymes originating from the proximal renal tubules. From the standard methods of the International Federation for Clinical Chemistry (IFCC), we used the kinetic method for the determination of alanine aminopeptidase (microsomal AAP), Î³-glutamyl transferase ((Î³-G) and MEIA (Microparticles Enzyme Immunoassay (Abbott A x sym system)) for determination of Î²2microglobulin in the urine. We examined samples (serum and urine) from 70 participants (35 Psa untreated, 35 healthy control group). RF and CRP were determined with the latex agglutination test in the same participants. Of the 35 examined patients with Psa, 12 (34.28%) showed presence of APP enzymuria, 8 patients (22.85%) showed presence of Î³-GT, and a low percentage (0% showed presence of Î²2-microglobulin in urine. AAP has a higher sensitivity thanÎ³-GT and Î²2-M in asymptomatic renal lesions in untreated Psa. Keywords : alanine aminopeptidase (AAP),Î³-GT (Î³-glutamyl transferase),Î²2-microglobulin (Î²2-M), spondyloarthropathies. https://doi.org/10.55302/JMS2361087s